Cara-cara mempercepat penyembuhan luka - takhfa nur asyifa; Syazili Mustofa; Helmi Ismunandar; Winda Trijayanthi (CV. Jasa Sukses Abadi, 2022)
A wound is a disconnection of tissue continuity due to damage, or loss of tissue substance due to injury or surgery. wounds are the most common injuries found in our daily lives. there are 3 phases of wound healing process are inflammatory phase, proliferation phase and maturation phase. this process is influenced by many factors like patient factors, wound factors and local factors. in the wound healing process, there are several things that can accelerate wound healing are away from cigarettes, reducing stress, improving nutrition by adding supplements (protein, vitamins and minerals), control chronic disease, stop consume alcohol, prevent infections (wound dressings and antibiotik), and avoid medical drugs that can affect wound healing. by understanding the physiology of good wound healing, we can accelerate wound healing and minimize unwanted effects